2013
DOI: 10.1016/j.ijporl.2012.09.037
|View full text |Cite
|
Sign up to set email alerts
|

A novel model of spontaneous otitis media with effusion (OME) in the Oxgr1 knock-out mouse

Abstract: Objective A novel mouse model with a specific genetic mutation in a G protein coupled receptor (GPCR) encoded by the oxgr1 gene results in a predisposition to spontaneous otitis media with effusion. As a primary component of interest in OME, mucin expression was examined in this model to assess expression as compared to wild type animals and suitability as a murine model of OME. Method Mutant (oxgr1−/−) and wild-type (oxgr1+/+) mice between ages of 2–5 months were examined by otoscopy and auditory brainstem … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
26
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 25 publications
0
26
0
Order By: Relevance
“…Notably, both wheel-running and ladder-climbing significantly increase circulating AKG (91.3 AE 3.7 lM versus 112.2 AE 3.2 lM; Fig 1I), indicating an enhanced OXGR1 activation induced by exercise. Previous studies have indicated that OXGR1 plays an important role in mucin regulation in otitis (Kerschner et al, 2013) and cardiac hypertrophy (Omede et al, 2016). However, there is no known role of OXGR1's effects on fat thermogenesis and lipolysis.…”
mentioning
confidence: 99%
“…Notably, both wheel-running and ladder-climbing significantly increase circulating AKG (91.3 AE 3.7 lM versus 112.2 AE 3.2 lM; Fig 1I), indicating an enhanced OXGR1 activation induced by exercise. Previous studies have indicated that OXGR1 plays an important role in mucin regulation in otitis (Kerschner et al, 2013) and cardiac hypertrophy (Omede et al, 2016). However, there is no known role of OXGR1's effects on fat thermogenesis and lipolysis.…”
mentioning
confidence: 99%
“…Recent genome-wide association studies identified MUC19 as a susceptibility gene of Crohn disease (119 -121). Muc19 expression is absent in the gastrointestinal tract of mice (21,122), as well as in cattle except for inconsistent and sparse expression in jejunum (123). MUC19 expression in the human gastrointestinal tract has not been studied extensively.…”
Section: Differences and Similarities In Expression Of Salivary Gelfomentioning
confidence: 99%
“…Heritability studies have shown that genetic factors can play an important role in otitis media susceptibility, but few contributing genes have been identified in human populations [1]. In contrast to human studies, a growing number of mouse mutations have been identified that manifest a high incidence of otitis media, including Eya4 , Tlr4 , p73 , MyD88 , Fas , E2f4 , Plg , Fbxo11 , Evi1 [1,2], Sh3pxd2b [3], Rpl38 [4], Isl1 [5], Chd7 [6], Lmna1 [7], Phex [8], Oxgr1 [9], Tgif1 [10], and Mcph1 [11]. The wide diversity of these genes and their mutant pathologies, including craniofacial abnormalities with Eustachian tube malformations and innate immune response defects, underscores the complex nature of otitis media.…”
Section: Introductionmentioning
confidence: 99%